MODEL OF HUMAN RESOURCE PERFORMANCE IMPROVEMENT BASED ON HUMAN CAPITAL AND SOCIAL CAPITAL WITH THE MODERATION OF INFORMATION TECHNOLOGY - Budiarti Ningrum (IJIBE (International Journal of Islamic Business Ethics), 2017)
This study investigates the effect of human capital and social capital on human resource performance, and the moderating effect of information technology. Based on a total sample of 88 respondents from the Technical Implementation Unit (UPT) of Monitor Radio Frequency Spectrum Class I Semarang and Yogyakarta which is analyzed using structural equation modeling based smartPLS 3.0, the results indicated that 1) human capital is positively related to social capital and human resorce performance; 2) social capital is positively related to human resorce performance; 3) information technology moderates the relationships between social capital and human resorce performance; and 4) information technology moderates the relationships between human capital and human resource performance.Keywords: Human capital, Social capital, Information technology, Human resource performance